SEME (SOCIAL AND ECOLOGYCAL MARKET ECONOMY) TERHADAP KEBERLANJUTAN SUMBERDAYA PERIKANAN DAN KESEJAHTERAAN NELAYAN - Ivonne Raystika Gretha Kaya; Sajriawati Sajriawati (Universitas Pattimura, 2023)
Fisheries resources are very vulnerable. Integrated management is needed between regions, sectors and stakeholders to sustain fisheries resources. Good management will provide the maximum benefits of the environment, economy and society.